Design, synthesis, biological evaluation and molecular docking of novel molecules to PARP-1 enzyme - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2019)
Poly (ADP-ribose) polymerase (PARP) enzyme catalyzes the transfer of ADP-ribose into target proteins. Therefore, PARP is responsible for DNA repair, cell proliferation, and cell death. In this study, potential PARP enzyme inhibitors were designed and synthesized. The synthesized compounds were elucidated by Fourier-transform infrared spectroscopy, H-1 NMR, C-13 NMR, heteronuclear single-quantum correlation, and mass spectrometry, and their purity was checked via thin-layer chromatography, high-performance liquid chromatography, and elemental analysis. A total of 63 newly synthesized compounds were screened in terms of PARP inhibition by cellular PARylation assay in the HeLa cell line. It was found that 19 compounds significantly inhibited the H2O2-induced cellular PARylation. The chemosensitizer effect of these compounds in cancer cells treated with doxorubicin (doxo) was investigated. It was found that the combination of potent PARP inhibitors with doxo potentiated a cytotoxic effect, similar to that of olaparib. The results of the molecular docking and absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis revealed that compound 60 might be classified as a potential PARP inhibitor candidate. Taken together, all of the results suggested that carbohydrazide derivatives could be a promising lead for the treatment for cancer disorders.
Keywords: PARP inhibitors; carbohydrazide; urea; molecular docking; ADMET; POLY(ADP-RIBOSE) POLYMERASE-1 INHIBITOR; CHEMOSENSITIZATION; DERIVATIVES; CANCER; CHARMM